Association studies of 19 candidate SNPs with sporadic Alzheimer’s disease in the North Chinese Han population - Yuan, Quan; Chu, Changbiao; Jia, Jianping (Neurological sciences, 2012)
Genome-wide association studies (GWAS) identified multiple single-nucleotide polymorphisms (SNPs) that are associated with the pathogenesis of Alzheimer’s disease (AD). As replication in independent studies remains the only way to validate proposed GWAS signals, we detect SNPs reported in the GWAS, in order to explore their association with sporadic AD (SAD) in the Chinese population. We analyzed genotype and allele distributions of 19 SNPs reported in GWAS in 191 SAD patients and 180 healthy controls. We found that higher frequencies of rs10868366 G and rs7019241 C carriers were observed in SAD patients compared with controls (rs10868366 G: P = 0.026, odds ratio (OR) = 1.4, 95% confidence intervals (CI) 1.0–1.9; rs7019241 C: P = 0.019, OR 1.4, 95% CI 1.6–1.9). Furthermore, rs10868366 G/T and rs7019241 C/T in GOLPH2 were in strong linkage disequilibrium and formed a relative protective factor rs10868366 T/rs7019241 T and a relative risk factor rs10868366 G/rs7019241 C. For SNP rs3826656 in near gene 5′ region of CD33, the results revealed that in subjects with APOE ε4 alleles, the A allele was associated with a reduced risk of SAD compared with the G allele (OR 0.479; 95% CI 0.263–0.870, P = 0.015), and AA genotype was associated with a reduced risk of SAD compared with the genotype AG + GG (OR 0.395; 95% CI 0.158–0.659, P = 0.008). Our results support the view that rs10868366 and rs7019241 in GOLPH2 and rs3826656 in near gene 5′ region of CD33 are significantly associated with SAD in the north Chinese Han population.